2003
DOI: 10.1097/01.lab.0000081388.40145.65
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression Pattern in Benign Prostatic Hyperplasia Infiltrating T Cells and Impact of Lymphocytic Infiltration on Cytokine mRNA Profile in Prostatic Tissue

Abstract: SUMMARY:The aim of the study is to characterize the type of immune response in benign prostatic hyperplasia (BPH) tissue.BPH tissue-derived T cells (n ϭ 10) were isolated, activated (PMA ϩ ionomycin), and analyzed for intracellular reactivity with anti-IFN-␥ and IL-2, -4, -5, -6, -10, and -13, as well as TNF-␣ and -␤ by four-color flow cytometry. Lymphokine release was tested using Th1/Th2 cytokine bead arrays. The amount of IFN-␥ and IL-2, -4, -13, and TGF-␤ mRNA expressed in normal prostate (n ϭ 5) was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 76 publications
3
110
0
Order By: Relevance
“…Partin et al 7 have demonstrated that doxazosin treatment resulted in caspase-3 activation within 24 h. Caspase-3 is a crucial enzyme for the executive phase of apoptosis that can be activated after the stimulation of tumor necrosis factor family receptors. Konig et al 26,27 have demonstrated that TNF-a can be one of the key factors in the benign prostate hyperplasia (BPH) pathogenesis. TNF-a induces cell death and cell proliferation within prostate tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Partin et al 7 have demonstrated that doxazosin treatment resulted in caspase-3 activation within 24 h. Caspase-3 is a crucial enzyme for the executive phase of apoptosis that can be activated after the stimulation of tumor necrosis factor family receptors. Konig et al 26,27 have demonstrated that TNF-a can be one of the key factors in the benign prostate hyperplasia (BPH) pathogenesis. TNF-a induces cell death and cell proliferation within prostate tissues.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A is secreted by a subclass of T helper cells (T H 17), linked to autoimmune prostatitis, and stimulates the expression of other cytokines and chemokines such as TNF-α, IL-6, and IL-8 (51,52). An earlier study could not demonstrate stimulatory activity on the proliferation of prostatic epithelial cells at the concentration of 20 ng/mL (53).…”
Section: Discussionmentioning
confidence: 99%
“…This shift is currently viewed as a counter-regulatory mechanism against inflammation, occurring when the Th1 response becomes dangerous for the host. Indeed, as testosterone lymphocytes progressively accumulate, IL4 and IL13 expression increases, suggesting a shift toward a Th0/Th2 immune response (Steiner et al 2003a). There is also evidence that a loss of tolerance to self-antigens, associated with expansion of Th17 cells and IL17 overexpression, is crucial in BPH development (Steiner et al 2003b).…”
Section: Introductionmentioning
confidence: 98%